Morphology of Right Atrioventricular Valve -A Postmortem Study - Sultana, Mahmuda; Islam, Md Tazul; Basak, Pran Krishna; Uddin, Md Samir; Sultana, Zakia (Medicine Today, 2020)
Introduction: Heart valves serve the important function of preventing backflow, or regurgitation, in the healthy heart. It is well known that cardiac valves can suffer from congenital and acquired disease. Most frequent acquired valvular abnormalities are stenoses of the aortic and mitral valves, which account for approximately 2/3rd of all valve disease. For the management of valvular disease morphology of right atrioventricular valve is essential. Materials and Methods: Study design was descriptive type of study. Place and period of study was Department of Anatomy, Sylhet MAG Osmani Medical College, Sylhet from July 2015 to June 2016. Results: Present study was performed on 70 post mortem human hearts of age ranging from 9 to 70 years. Human heart was collected from the unclaimed dead bodies autopsied in the department of Forensic medicine in Sylhet MAG Osmani Medical College during the study period fulfilling the inclusion criteria. Conclusion: The collected samples were divided into 3 groups depending on age. Group – A: (9 - 21 Years), Group - B: (22 - 41 Years), Group - C: ( 42 -70) Years. Each group was subdivided into two groups depending on their sex. Medicine Today 2020 Vol.32(1): 42-44